Decalogue for open and strategic social innovation - Calzada, I (Translokal Academic Entrepreneurship, 2016)
As a result of the workshop and wrapping up the strategic content in the social innovation field that Fomento San Sebastian has been developing so far, the following report was written by Dr Calzada.